Improved early season management of sub1 rice varieties enhances post-submergence recovery and yield - Banayo, Niño P. M.; Mabesa-Telosa, Ranee C.; Singh, Sudhanshu; Kato, Yoichiro (Cambridge University Press, 2019)
More than 10 Sub1 rice varieties carrying the submergence-tolerance gene have been released for flood-prone environments in tropical Asia. Improved management practices have been shown to enhance yields of these varieties. The objective of this study was to dissect the growth response of IR64-Sub1 to integrated crop management in a flash flood at the late vegetative stage. Field experiments were conducted at the International Rice Research Institute, Philippines in the dry and wet seasons of 2013. Complete submergence was imposed for 14 days starting at 37 days after transplanting. Integrated management practice (IMP) consisting of: (i) application of fertilizer (compared with no fertilizer use in conventional practice), (ii) use of lower seeding rate (400 vs. 800 kg ha−1) in the nursery bed, (iii) use of slightly older seedling for transplanting (30 vs. 18 day-old), and (iv) higher planting density (33.3 vs. 25.0 hills m−2) gave yields higher by 8–87% compared with the conventional practice (1.3–2.4 t ha−1) in both seasons. This was attributable to higher shoot biomass after water recession, more tillers m−2, greater leaf area expansion and shoot biomass accumulation during the recovery period, and higher filled-grain percentage at maturity. The improved management had no positive effect on panicle formation, spikelets panicle−1, and harvest index since stress was imposed at the transition period between vegetative and reproductive phases. Our results suggest the appropriate nursery management, for submergence-resilient seedlings to further alleviate damage caused by flash floods and increase the yield of Sub1 varieties in flood-prone rainfed lowlands.